2019
DOI: 10.32677/ijch.2019.v06.i05.005
|View full text |Cite
|
Sign up to set email alerts
|

Study of risk factors, clinical profile, and outcome in meconium-stained deliveries

Abstract: Background: The presence of meconium in amniotic fluid is a serious sign of fetal distress which leads to an increase in neonatal mortality. Objective: The objective of this study was to study the risk factors, clinical profile, and outcome of babies born through meconium-stained fluid. Materials and Methods: This prospective observational study was conducted during the period from February 2018 to October 2018 at neonatal unit of a tertiary care hospital. All live babies delivered through meconium-stained liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The association between fetal distress and MSAF has been reported in many studies [8]. Shukla and Swapna's observed that 23.7 percent of patients with the MSAF exhibit fetal distress [9].…”
mentioning
confidence: 79%
“…The association between fetal distress and MSAF has been reported in many studies [8]. Shukla and Swapna's observed that 23.7 percent of patients with the MSAF exhibit fetal distress [9].…”
mentioning
confidence: 79%
“… 4 - 6 The most common complication of MAS is Respiratory distress and other morbidities were convulsions, sepsis, shock, hypoxic-ischemic encephalopathy, hyperbilirubinemia and hypoglycemia. 13 …”
Section: Discussionmentioning
confidence: 99%
“…Meconium-stained amniotic fluid not only poses risk to the newborn but also significantly increases the rate of maternal complications such as meconium-laden amniotic fluid embolism, intrapartum chorioamnionitis, puerperal endometritis, wound infection, increased risk of operative delivery and its complication. 13 , 14 The perinatal morbidity and mortality related to MSAF can be decreased if major risk factors are recognized early and closely monitoring of the labour and careful decisions are made about the timing and mode of delivery. 14 …”
Section: Discussionmentioning
confidence: 99%